Critical and Strategic Metal Resources of Greece - Tsirambides, Ananias; Filippidis, Anestis (Bulletin of the Geological Society of Greece, 2024)
Greece has a large number of critical and strategic metal resources. The proven and indicated reserves of aluminum amount to 2.5 mt and their gross value €5.075 b. Those of chromium amount to 1.2 mt with gross value €4.320 b, while of cobalt are 129 th. t with gross value €3.348 b. The proven and indicated reserves of copper from Chalkidiki and Kilkis areas are approximately 3.04 mt and their gross value €24.776 b, while those of manganese are 2.25 mt with gross value €5.400 b. Molybdenum has been located in Pigi Kilkis with indicated reserves of about 7.7 th. t and gross value €326 m. Under mining are the vein type magnesite deposits of Gerakini Chalkidiki and North Evia. The total reserves (proven + indicated) of magnesite are 280 mt and their gross value €9.800 b. The most important lateritic Fe-Ni-bearing ores are those of Evia Island, Agios Ioannis Viotia, Lokrida Fthiotida, Mesopotamia and Ieropigi Kastoria. The proven and indicated reserves of nickel are 1.39 mt and their gross value €22.240 b. The Rizana/Lachanas porphyry-epithermal antimony deposit is considered the most important stibnite ore. The proven and indicated reserves of stibnite are at least 100 th. t with an average Sb content of 0.3 wt%. Copper, chromium, and cobalt present good prospects for mining. Platinum group metals (PGMs), with economic interest, are contained in the porphyry Cu deposits of Skouries Chalkidiki. Strymonikos Gulf, together with the neighboring coastal and submarine sands, is the most probable area for locating exploitable rare earth metals (REMs). There are excellent investment opportunities in the exploration and mining of Bi, Te, Ga, Ge, and In metals. The deposits of other critical and strategic metals of Greece should be adequately assessed.